Images from the Region of the Pueblo Indians of North America - Warburg, Aby M. (Cornell University Press, 2016)
Aby M. Warburg (1866-1929) is recognized not only as one of the century's preeminent art and Renaissance historians but also as a founder of twentieth-century methods in iconology and cultural studies in general. Warburg's 1923 lecture, first published in German in 1988 and now available in the first complete English translation, offers at once a window on his career, a formative statement of his cultural history of modernity, and a document in the ethnography of the American Southwest. This edition includes thirty-nine photographs, many of them originally presented as slides with the speech, and a rich interpretive essay by the translator.